Foreword From Editors - 18th Edition: Emerging Cross-Cultural Collaborations, Hands-On Learning and Participation - Yatmo, Yandi Andri; Paramita, Kristanti Dewi; Suryantini, Rini (ASEAN Journal of Community Engagement, 2025)
This edition of AJCE exemplifies how cross-cultural collaborations and hands-on learning and participation can foster a better and more meaningful process of community engagement. The cross-cultural collaborations enable the co-production of knowledge and creativity between stakeholders from different cultures, in addition to creating cultural competence where people from different realities treat and support others with sensitivity and respect. The hands-on learning process encourages a deeper engagement where stakeholders are more responsive to the reality of the situation they are in and therefore creates better agility for adaptations towards various issues or adoptions of new skills. By focusing on cross-cultural collaborations and hands-on learning, we aim to present how the articles in this issue promote a future agenda of community engagements that are more globalised, culturally competent, and attuned to the realities. Through such an agenda, these studies broaden the discourse on community engagement towards a more equitable and active participation across societies.